Entangled subjects : Indigenous/Australian cross-cultures of talk, text, and modernity - Grossman, Michele, 1957- (Cross/cultures, 2013)
Indigenous Australian cultures were long known to the world mainly from the writing of anthropologists, ethnographers, historians, missionaries, and others. Indigenous Australians themselves have worked across a range of genres to challenge and reconfigure this textual legacy, so that they are now strongly represented through their own life-narratives of identity, history, politics, and culture. Even as Indigenous-authored texts have opened up new horizons of engagement with Aboriginal knowledge and representation, however, the textual politics of some of these narratives - particularly when c.